PEMBUATAN KECAP IKAN DARI IKAN BULU AYAM (Coilia dussumieri) DENGAN METODE HIDROLISIS ENZIMATIS MENGGUNAKAN SARI NANAS - Kurnia Sada Harahap; Apri Mujiyanti; Lia Novita Sari (Universitas Teuku Umar, 2020)
Fish sauce is a fermented product in the form of a dark brown liquid, it tastes relatively salty or sweet and smells good. The process of making fish sauce requires a long time. The proteolytic enzyme addition before fermentation can shorten the time in making fish sauce. The purpose of this study was to determine the fermentation process fish sauce from chicken feather by using enzymatic hydrolysis with pineapple juice, the effect of adding pineapple juice and fermentation time and to determine the results of the enzymatic organoleptic test and the most preferred by panelists. The method used in this research is an experimental quantitative method. Data analysis was done by using a completely randomized design (CRD). From the results of this study, the fermentation process of chicken feather fish sauce by adding different pineapple extract (25%, 50% and 75%) from the weight of fish meat with fermentation time of 3 days, 6 days, 9 days, 12 days and 15. day. The analysis of the chicken feather fish sauce was done by using sensory (smell, taste, color and thickness). The best research results was obtained by increasing the concentration of pineapple extract by 25% at the fermentation time of 9 days with the criteria of unique, sweet flavor and brownish fish sauce that panelists like from the addition of a concentration of 25% pineapple extract at the fermentation time of 9 days in the fish sauce. This shows that the addition of pineapple juice extract can accelerate the fermentation process besides affecting the preferred hedonic value. Keywords: Bromelain enzyme, Fermentation, Bulu ayam fish, Fishsauce